Analisis Strategi Pemasaran Kewirausahaan Umkm Pusat Kebugaran (Studi Kasus “Kenanga Fitness” Di Bandar Lampung Provinsi Lampung) - Daud, Syahril; Narmade, Ketut; Hernanta, Made Dicky; Sena, Bielsa Diva (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The purpose of this study was to determine how marketing tactics such as distribution, price, promotion, and product affect the level of client loyalty. Google Forms was used to survey Kenanga Fitness customers as part of the quantitative methodology of this study. Multiple linear regression, validity, reliability, and classical assumptions were used to test the data. The study's findings indicate that distribution, pricing, promotion, and product strategies all have a significant impact on consumer loyalty. Suggestions are made to maximize the use of digital technology and improve customer relationships through more effective marketing techniques.